Representation of Femininity in Indonesian Folklore - Sugiarti; Lestari, Fitri Anggun (Universitas Muhammadiyah Malang, 2023)
At the level of social life, the issue of femininity and masculinity is still a serious topic of discussion because in the construction of patriarchal culture, there is still a clear dichotomy. Femininity in Indonesian folklore is interesting to study because it presents a female figure who is different from the reality of society and who is able to deconstruct herself. The research objectives are to reveal (1) the role of femininity in female characters in building of themselves and the environment and (2) the strength of female characters' femininity in building their self-image as dignified beings. The method used in this research is a descriptive method, namely describing the issue of femininity in folklore. The approach used in this research is feminist, an approach that emphasizes the image of women and stereotypes of women in literary works. The research data are story sequences in the form of sentences and paragraphs that describe the values of femininity in Indonesian folklore. Data collection techniques were conducted through documentation studies include classifying and categorizing data, as well as critical and creative reading and finding the power of feminism in stories. Research data analysis techniques are carried out by understanding the meaning of the text in depth, observing and exploring the message, and analyzing it interactively and dialectically for the accuracy of the findings. The results show that (1) the role of femininity of female characters in Indonesian folklore is seen in how women develop themselves and the environment, which is marked by the appearance of empowered characters; and (2) the strength of femininity possessed by female characters in building their self-image as dignified beings is shown in their ability to carry out their duties in the domestic and public spheres in a balanced manner. Women's intelligence and ingenuity are demonstrated in developing strategies for dealing with problems. Moreover, women have strong authority and independence. The conclusion that can be drawn is that the representation of femininity in Indonesian folklore is that female characters are able to position themselves with the strength built by themselves and their environment.